From Standing Rock to flint and beyond: resisting neoliberal assaults on indigenous, maroon, and other sites of racially subjected community sustainability in the Americas - Harrison, Faye V. (Abya-yala: Revista sobre Acesso à Justiça e Direitos nas Américas, 2018)
Protests against the Dakota Access Pipeline led by water protectors from the Standing Rock Sioux Tribe in North Dakota have brought human rights violations related to Indigenous sovereignty, environmental justice, and sustainable development into the foreground of political debate in the United States. The struggle at Standing Rock has been strengthened by a coalition formed with activists from other Indigenous Nations, including representatives from the Amazon Basin, and from non-Indigenous movements and political organizations such as the Green Party and #BlackLivesMatter. This article reflects upon the centrality of Indigenous Sovereignty within the broader struggle for human rights and democracy in their most inclusive and substantive senses, especially in societies whose development has been built upon the violence of colonial expansion, white supremacy, and heteropatriarchy. The article also situates Indigenous rights within regimes of multiple articulated alterities in which the subjugation and dispossession of Indigenous and Afro-descendant peoples have been historically differentiated yet intertwined in the Americas. The article offers a multi-sited framework for understanding the convergent and divergent points of reference in the logics of Indigenous and Afro-descendant identity, the relationship with the State and Market, and connections to the material and spiritual resources of land. Attention is directed to cases in the United States, Honduras, and Suriname (including those of communities that define themselves as “Afro-Indigenous”) in which some notion of common ground, affinity, or alliance with past or present-day Indigenous peoples has been mobilized in Afro-descendants’ collective claims on rights to land, development, and cultural resources.